Financial Planning and Control Practices of Selected Non-Governmental Organizations: An Empirical Appraisal - Karanth, Bharathi (Indian Journal of Finance, 2016)
Non-governmental organizations have an immense role in the achievement of Millennium Development Goals, an initiative of United Nations. It is especially true in the case of a developing country like India. The spread of NGO activities in the country is manifested in a number of spheres and in a wide spectrum of programs. The participation of the NGO sector has been impressive in welfare programs, development-oriented initiatives, empowering women and weaker sections, protecting the rights of marginalized segments, protecting the environment, spreading literacy and education, and so forth. Funds do flow into these non-governmental organizations both from the internal sources as well as from the external sources. However, efficient utilization of the funds and the accountability towards the different stakeholders are found to be the lowest among the NGOs. Non-governmental organizations need to have sound financial management practices, both at the organizational level and within social programs to accomplish the basic purpose for which they have been set up. This study sought to explore the financial priorities, financial planning, and control practices of non-governmental organizations in Dakshina Kannada and Uttara Kannada districts in the state of Karnataka. This study is explorative in nature. The study revealed that the transparency regarding the financial practices followed in the NGOs was not highly appreciable, but NGOs were aware and had a positive bent of mind towards implementing better financial practices in their operations.